An Empirical Analysis of Determinants of Capital Adequacy Ratio for the Banks in Pakistan - Sandhu, Amna (2017)
Given the significant role that Capital levels play in the banking industry during economic distress, this paper aims to investigate how the banks in Pakistan determine capital ratio. The paper starts with evaluating the performance of Pakistani banks over the period of 2011-2016 using a Stochastic Frontier Approach to estimate cost-efficiency scores and scale economies. This is followed by a GMM framework used to define and analyse the nature of capital determinants in the context of Pakistan. Lastly, the paper uses impulse-response functions to verify the granger-causality between banks capital ratio and performance. The results suggest that liquidity risk, size, asset quality and performance are significant determinants of CAR in the context of Pakistan. This paper aims to help policymakers to formulate appropriate regulations for the banks in Pakistan.